Glucocorticoid Receptor Antagonism Upregulates Somatostatin Receptor Subtype 2 Expression in ACTH-Producing Neuroendocrine Tumors: New Insight Based on the Selective Glucocorticoid Receptor Modulator Relacorilant - Pivonello, Rosario; Munster, Pamela N.; Terzolo, Massimo; Ferrigno, Rosario; Simeoli, Chiara; Puglisi, Soraya; Bali, Utsav; Moraitis, Andreas G. (Frontiers in Endocrinology, 2022)
Somatostatin exhibits an inhibitory effect on pituitary hormone secretion, including inhibition of growth hormone and adrenocorticotropic hormone (ACTH), and it can have antisecretory and antitumor effects on neuroendocrine tumors (NETs) that express somatostatin receptors. Although the precise mechanism remains unclear, the finding that glucocorticoids downregulate somatostatin receptor subtype 2 (SSTR2) expression has been used to explain the lack of efficacy of traditional SSTR2-targeting analogs in patients with ACTH-secreting NETs. Glucocorticoid receptor (GR) antagonism with mifepristone has been shown to reverse the glucocorticoid-induced downregulation of SSTR2; however, the effects of GR modulation on SSTR2 expression in ACTH-secreting NETs, particularly corticotroph pituitary tumors, are not well known. The current study presents new insight from in vitro data using the highly selective GR modulator relacorilant, showing that GR modulation can overcome dexamethasone-induced suppression of SSTR2 in the murine At-T20 cell line. Additional data presented from clinical case observations in patients with ACTH-secreting NETs suggest that upregulation of SSTR2 via GR modulation may re-sensitize tumors to endogenous somatostatin and/or somatostatin analogs. Clinical, laboratory, and imaging findings from 4 patients (2 ACTH-secreting bronchial tumors and 2 ACTH-secreting pituitary tumors [Cushing disease]) who were treated with relacorilant as part of two clinical studies (NCT02804750 and NCT02762981) are described. In the patients with ectopic ACTH secretion, SSTR2-based imaging (Octreoscan and 68Ga-DOTATATE positron emission tomography) performed before and after treatment with relacorilant showed increased radiotracer uptake by the tumor following treatment with relacorilant without change in tumor size at computed tomography. In the patients with Cushing disease who received relacorilant prior to scheduled pituitary surgery, magnetic resonance imaging after a 3-month course of relacorilant showed a reduction in tumor size. Based on these findings, we propose that GR modulation in patients with ACTH-secreting NETs upregulates previously suppressed SSTR2s, resulting in tumor-specific antisecretory and anti-proliferative effects. The effect of relacorilant on pituitary corticotroph tumors is being investigated in an ongoing phase 3 study (NCT03697109; EudraCT 2018-003096-35).